Opportunities for rail in the transport of carbon dioxide in the United States - Ho, Alina; Giannopoulos, Diamantoula; Pilorgé, Hélène; Psarras, Peter (Frontiers in Energy Research, 2024)
The deployment of carbon management strategies like carbon capture and storage (CCS) and carbon dioxide removal (CDR) at scale will require significant investments in transport infrastructure to deliver CO2 to reliable storage. While pipeline transport has dominated the conversation due to economic reasons, there is increasing evidence that other modes may become viable alternatives when considering scale, regional opportunities, and social acceptance. This paper assesses the viability of rail for CO2 transport in the United States using market analysis, techno-economic assessment and geographic information systems mapping. We believe rail presents many advantages, notably in existing infrastructure with established right-of-ways, but also as an instrument to address unwanted effects of our energy transition, particularly in coal communities. We find that the strategic replacement of coal as a freight commodity could translate into 100 Mt/yr of CO2 movement by rail by 2050, and support up to 60,000 jobs in that industry. Further, we find that while rail pricing is notoriously volatile, there is strong support for rail being the least cost option over pipeline for volumes under 2 Mt CO2 per year, which aligns well with smaller, more risk-averse, and distributed carbon management projects that are scheduled to deploy over the next decade. Rail can also be an alternative in regions where CO2 pipeline projects have had limited success, like in the Midwest, where CO2 is captured from ethanol plants that are already serviced by rail networks. Likewise, rail can service roughly 25% of point-source CCS opportunities that are not proximal to projected trunk pipeline networks, of which 94% are located 1-mile from railroad. Finally, rail may be an integral part of CDR development in regions that are not coterminous with geologic storage, particularly in the Western and Northern US.